Uji Aktivitas Antioksidan Lotion Ekstrak Etanol Daun Pepaya (Carica papaya L.) - DEVAHIMER HARSEP ROSI, DEVAHIMER HARSEP ROSI; Afriani, Tika; Alysa Putri, Hasnah (SITAWA : Jurnal Farmasi Sains dan Obat Tradisional, 2023)
Papaya leaves contain phytochemical including alkaloid, saponin, tannin, flavonoid, triterpenoid, and asiaticoside glycoside. Flavonoid compounds in papaya leaves function as antioxidant that can capture free radicals. This study aims to determine the ethanol extract of papaya leaves can be formulated into lotion preparation and to test the antioxidant activity of these preparation. This study used an experimental method of lotion preparation made with varying concentrations of papaya leaf ethanol extract 2g (F1), 4g (F2), 6g (F3). Physical evaluation include organoleptic test, homogeneity test, pH test, irritation test, spreadability test, and antioxidant activity test. All formulas met the physical evaluation requirements. The papaya leaf ethanol extract lotion has the highest IC50 value, namely at F3 of 44.72 ppm in the very strong antioxidant category.